2020
DOI: 10.1002/hep4.1491
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in Populations With Liver‐Related Diseases in the Middle East and North Africa

Abstract: We investigated hepatitis C virus (HCV) epidemiology in populations with liver‐related diseases (LRDs) in the Middle East and North Africa. The data source was standardized databases of HCV measures populated through systematic reviews. Random‐effects meta‐analyses and meta‐regressions were performed, and genotype diversity was assessed. Analyses were based on 252 HCV antibody prevalence measures, eight viremic rate measures, and 30 genotype measures on 132,358 subjects. Pooled mean prevalence in LRD populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For instance, province or city of birth and/or current residence, prior exposure to an HCV mode of transmission 22 , or history of HCV infection in the family, could be added, among others. Given that the risk of exposure to HCV infection varies immensely by at-risk subpopulation type and shows a distinctive hierarchy 23 , an additional component to the score could be to integrate the at-risk subpopulation type as a variable 23,24 , thereby further enhancing the diagnostic accuracy of the score. Testing strategies, therefore, could be highly efficient in identifying HCV infected persons at a modest cost.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, province or city of birth and/or current residence, prior exposure to an HCV mode of transmission 22 , or history of HCV infection in the family, could be added, among others. Given that the risk of exposure to HCV infection varies immensely by at-risk subpopulation type and shows a distinctive hierarchy 23 , an additional component to the score could be to integrate the at-risk subpopulation type as a variable 23,24 , thereby further enhancing the diagnostic accuracy of the score. Testing strategies, therefore, could be highly efficient in identifying HCV infected persons at a modest cost.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of HCV epidemiology in the Middle East found a pooled mean prevalence of 35.5% (95%CI: 31.7%-39.5%) in all patients with LDs; the highest rates were estimated for HCC (56.9%; 95%CI: 50.2%-63.5%) and hepatic cirrhosis (50.4%; 95%CI: 40.8%-60.0%). The pooled rate was 58.8% (95%CI: 51.5%-66.0%) in Egypt, 55.8% (95%CI: 49.1%-62.4%) in Pakistan, and 15.6% (95%CI: 12.4%-19.0%) in other countries[ 88 ]. The rate of HCV infection in each LD population of each country was strongly correlated with HCV prevalence among their GP.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of HCV infection in each LD population of each country was strongly correlated with HCV prevalence among their GP. The authors concluded that their findings highlight how the role of this infection in liver diseases is a reflection of its background level in the GP[ 88 ]. Moreover, in countries like Egypt and Pakistan, high rates of infections among various populations with LDs may support the contribution of HCV to the occurrence of liver disease[ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 OCI has been described in patients with chronic liver disease, coinfections, comorbidities and in population with risk factors, such as, in patients infected with hepatitis B virus or human immunodeficiency virus, with tattoos, drugs users, and apparently in healthy population. [6][7][8][9][10][11] The primary goal of HCV therapy is to cure the infection, i.e. to achieve a sustained virological response (SVR) defined as undetectable HCV-RNA in serum after treatment completion, and the use of direct-acting antiviral agents (DAAs) markedly improved the SVR rates.…”
Section: Introductionmentioning
confidence: 99%